BANDS NEUTROPHILS LEVELS CHARACTERIZATION AND THEIR DYNAMICS AT TREATMENT OF ACUTE ALIMENTARY PANCREATITIS PATIENTS - Avdosiev, Y. V.; Pankiv, K. M.; Khimich, S. D.; Belozоrov I. V.; Kudrevych, O. M.; Khytruk, S. V.; Ustymenko, O. S.; Iaremchuk, P. V. (Modern medical technology, 2019)
Purpose of the study. To evaluate changes of bands nuclear neutrophils level and their dynamics parameters during treatment in patients with acute alimentary pancreatitis based on repeated measurements and taking into account the severity of the course. Materials and methods. Seventy patients with acute alimentary pancreatitis were examined, who treated in Surgical Department of Vinnitsa Regional M. I. Pirogov Clinical Hospital. Average age was 45,4 ± 13,87 years. Severe pancreatitis was found in 34 (48,57%) people, in 25 (35,72%) – moderate, 11 (15,71%) persons had mild forms. The severity of the disease was assessed using the Atlanta classification (2012). To achieve aim of study the repeated measurements of the stabs neutrophils levels were performed for all patients. Statistical analysis was performed using STATISTICA 13. Results. The significant difference between the stabs neutrophils values identified in patients with acute alimentary pancreatitis was proved, taking into account the severity of the course, both during the primary measured (p = 0,04), during treatment (p = 0,004), and after its completion (p < 0,00001). The significant increase of stabs neutrophils level associated with increasing severity of acute pancreatitis, as in the primary treatment of patients (τ = 0,23, p = 0,005), with determination during treatment (τ = 0,31, p = 0,0001) and after its termination (τ = 0,49, p  0,00001) was determined. When comparing the indexes of stabs neutrophils determined by repeated measurements, a rapid and continuous decrease of their values was found, as a whole in the group – by 3,76 times, and in the groups with a mild course of the inflammatory process – 6,75 times, the average degree of severity – in 5,11 times and severe forms – 3,05 times. Conclusions. Highinformativenessofevaluation stabs neutrophils level and their dynamic during repeated measurements in patients with acute alimentary pancreatitis taking into account the severity of the course has been proved.